(untitled) (Research, Society and Development, 2021)
In recent years, the consumption of medicinal plants and herbal medicines has experienced a notable increase in consumption in Brazilian society. This is due to the fact that the safety demonstrated by clinical studies is its effectiveness in the treatment of certain pathologies. In addition to the perception of safety of these products by prescribers and lay society, at the same time they are increasingly present in pharmacies and drugstores, increasing the therapeutic arsenal of these establishments. This study aims to analyze the labels of herbal medicines sold in a drugstore in the city of Manaus-AM, in relation to what is recommended by the current legislation of Anvisa. The present study is a sampling research with comparative data analysis of 35 herbal medicines, using data published by Anvisa referring to the labeling of herbal medicines. The present study demonstrated that not all medications follow the standardization of Anvisa, since the Braille system is largely lacking, which makes people with visual impairments unable to access it. The data presented show a significant amount of herbal medicine brands do not meet this essential demand, that is, the guarantee of access for the visually impaired to safe and rational therapy of herbal medicines, with only 29% of the analyzed medicines being compatible with what is recommended by ANVISA legislation. Works like this have an important role to be monitored in social demands, and should be further explored, since they provide an immense inspection service to regulatory bodies and lay society.